Tolerogenic Transcriptional Signatures of Steady-State and Pathogen-Induced Dendritic Cells - Vendelova, Emilia; Ashour, Diyaaeldin; Blank, Patrick; Erhard, Florian; Saliba, Antoine-Emmanuel; Kalinke, Ulrich; Lutz, Manfred B. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are key directors of tolerogenic and immunogenic immune responses. During the steady state, DCs maintain T cell tolerance to self-antigens by multiple mechanisms including inducing anergy, deletion and Treg activity. All of these mechanisms help to prevent autoimmune diseases or other hyper-reactivities. Different DC subsets contribute to pathogen recognition by expression of different subsets of pattern recognition receptors, including Toll-like receptors or C-type lectins. In addition to the triggering of immune responses in infected hosts, most pathogens have evolved mechanisms for evasion of targeted responses. One such strategy is characterized by adopting the host's T cell tolerance mechanisms. Understanding these tolerogenic mechanisms is of utmost importance for therapeutic approaches to treat immune pathologies, tumors and infections. Transcriptional profiling has developed into a potent tool for DC subset identification. Here, we review and compile pathogen-induced tolerogenic transcriptional signatures from mRNA profiling data of currently available bacteria- or helminth-induced transcriptional signatures. We compare them with tolerogenic steady-state DC subtypes to identify common and divergent strategies of pathogen induced immune evasion. Candidate molecules are discussed in detail. Our analysis provides further insights into tolerogenic DC signatures and their exploitation by different pathogens.